MANAJEMEN PELAYANAN UMAT PADA MASJID AL-FURQON DESA HAURGEULIS KECAMATAN HAURGEULIS KABUPATEN INDRAMAYU - Eman Suherman; Asrof Fitri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
A mosque is a religious institution that is inseparable from the spiritual, social and cultural life of Muslims. However, at present, the existence of some mosques is increasingly experiencing a narrowing of their roles and functions, from the service center of the people to being merely a complementary worship facility in various places. Masjid Al-Furqon Haurgeulis is located in an area where community activities are quite dense, including the center of government activities at the sub-district level, education, markets and train stations. This study aims to determine, describe, and analyze how service management at the Al-Furqon Mosque is in service to the people in Haurgeulis, especially covering aspects of education, social society, and economic development of the people. This study uses a qualitative descriptive research methodology, namely by conducting research that produces descriptive data in the form of written or spoken words from people and observed behavior. The results of this study can be concluded that the service management system of the Al-Furqon Haurgeulis Mosque has implemented good management functions which include predetermined planning, organizing, executing what has been planned and monitoring by setting standard measures of supervision and evaluation is carried out by discussing a whole series of activities.